Relationship between knowledge of parents and depression in school age in Babylon City (Eurasian Medical Research Periodical, 2022)
This is a descriptive study that aimed to relationshp between parent of knowledge toward depression , data was collected in Al-qassim hospital by questionnaire from ,data analysis by frequency and percentage ,results shows that (28%) of parents their level education ,read and write , also the results shows that (76%) of parents not working . the results shows that (60%) economic state of family were moderate .and shows that (52%) of child age between (10-12)years . the study shows (56%)of child were male .and resuts shows that (84%) of child feel of the sadness and of them have sleep disorder ,the study shows that also (52%) of child have loss of weight.so the researcher recommended to do educational program for the parents regarding depression